1990
DOI: 10.1095/biolreprod43.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Progesterone Antagonist, Lilopristone (ZK 98.734), on Induction of Menstruation, Inhibition of Nidation, and Termination of Pregnancy in Bonnet Monkeys

Abstract: The effects of a progesterone antagonist, lilopristone (ZK 98.734), on induction of menstruation, inhibition of implantation or pregnancy, and termination of early and mid-pregnancy were studied in bonnet monkeys. In the regularly menstruating animals, administration of lilopristone (25 mg/day, s.c.) during the mid-luteal phase (Days 20-22 of the menstrual cycle) induced menstruation within 2-4 days after the initiation of treatment. A premature drop in circulating progesterone levels was also observed. The lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The crucial role of progesterone in endowing the endometrium with receptivity has been substantiated in several reports demonstrating retardation in endometrial development and subsequent implantation failure when progesterone actions were neutralized using antiprogestins such as RU 486 (mifepristone) [8,9], ZK 98.299 (onapristone) [10][11][12], or ZK 98.734 (lilopristone) [13] in primates. These antiprogestins compete with progesterone for its binding site on PR and, once bound, make the receptor nonfunctional by inducing conformational changes.…”
Section: Introductionmentioning
confidence: 95%
“…The crucial role of progesterone in endowing the endometrium with receptivity has been substantiated in several reports demonstrating retardation in endometrial development and subsequent implantation failure when progesterone actions were neutralized using antiprogestins such as RU 486 (mifepristone) [8,9], ZK 98.299 (onapristone) [10][11][12], or ZK 98.734 (lilopristone) [13] in primates. These antiprogestins compete with progesterone for its binding site on PR and, once bound, make the receptor nonfunctional by inducing conformational changes.…”
Section: Introductionmentioning
confidence: 95%
“…(11 ß-[4-dimethyl-amino phenyl]l7ß-hydroxy-l7fX- [l-propynyl] estra-4,9-dien-3-one) is a 19-norsteroid with potent antiprogesterone and antiglucocorticoid activities (Baulieu, 1989), and it reduces maternal progesterone concentrations in several species including pigs, cattle, monkeys (Rhesus and Macaca fascicularis), and humans (Nieman et al, 1987; Baulieu, 1989;Puri et receptors and such binding either blocks the interaction between progesterone receptors and DNA or impairs gene transactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated an early decline in the progesterone concentration and premature menstruation following treatment with ZK 98.299 or ZK 98.734 in bonnet monkeys (36,37). Treatment with these antiprogestins induced early menstruation during HCG induced pseudopregnancy in bonnet monkeys (37). Treatment of bonnet monkeys with high doses of onapristone for 7 consecutive cycles led to decreased LH secretion, impaired folliculogenesis, anovulation and endometrial retardation (38).…”
Section: Structural Remodelling Of Endometriummentioning
confidence: 97%